Diversity and Skill Learning (A Review of Inclusive Models in Arabic Language Education) - Edy Sulaiman; M. Mansyur (Maharot : Journal of Islamic Education, 2022)
This research aims to analyze an inclusive Arabic language learning model. The study utilizes a qualitative approach with a literature review type focusing on scholarly literature discussing the topic. Data sources include academic literature such as reference books and published journal articles. Content analysis is employed for data analysis. The results of this research indicate that: First, student diversity in the inclusive Arabic language learning model encompasses a profound understanding of students' diversity in terms of cultural background, abilities, learning styles, and special needs. Second, the development of Arabic language skills in the inclusive learning model provides an overview of the extent to which this model supports students in achieving desired competencies, including listening, speaking, writing, and reading.